Exposing Discrepancies in Indonesia's Legislative Processes: Mengungkap Ketidaksesuaian dalam Proses Legislasi di Indonesia - Mannan, Faidhul; Ramzy, Isvandiar Muhammad; Rato, Dominikus; Setyawan, Fendi (Universitas Muhammadiyah Sidoarjo, 2024)
This study critically examines the application of Indonesia’s Law Number 12 of 2011, which governs legislative processes with principles aimed at ensuring clarity, justice, and accountability. Utilizing a normative research method, the analysis synthesizes relevant literature and legal documents to explore the practical implementation of these principles. The findings reveal significant discrepancies between the theoretical framework and its practical execution, suggesting that while the law establishes a robust basis for legislation, its effectiveness is hindered by gaps in application. This research underscores the need for policy refinement and offers actionable insights for enhancing the functionality and integrity of legal systems globally. Highlights: Theory vs. Practice Gap: Reveals discrepancies between legislative principles and their real-world application. Legal Framework Effectiveness: Discusses how implementation gaps impact legal integrity. Policy Improvement Suggestions: Provides recommendations for enhancing legislative processes. Keywords: Policy Implementation, Legal Integrity, Principles, Concepts, Legislation